Soil Health and Its Improvement Through Novel Agronomic and Innovative Approaches - Shahane, Amit Anil; Shivay, Yashbir Singh (Frontiers in agronomy, 2021)
Soil is an important natural resource providing water, nutrient, and mechanical support for plant growth. In agroecosystem, continuous manipulation of soil is going on due to addition of input, removal of nutrients, changing water balance, and microbial life. These processes affect soil properties (physical, chemical, and biological), and the deviation of these properties from the normal status is controlled by soil buffering capacity and soil resilience. If these changes are beyond the reach of soil resilience, then soil loses its original state, leading to soil degradation. At present, the extent of the degraded area in the world is 1,036 to 1,470 million ha. This urges the need for maintaining soil health rather than the mere addition of input for crop production. Soil health is an integrative property that reflects the capacity of soil to respond to agricultural intervention, so that it continues to support both agricultural production and the provision of other ecosystem services. Maintaining the physical, chemical, and biological properties of soil is needed to keep it healthy, and this is possible through the adoption of different agronomic approaches. The diversification of nutrient sources with emphasis on organic sources, adoption of principles of conservation agriculture, enhancement of soil microbial diversity, efficient resource recycling through the integrated farming system, and amendment addition for correcting soil reactions are potential options for improving soil health, and are discussed in this review. This article reviewed the concept of soil health and its development, issues related to soil health, and indicators of healthy soil. At the same time, the impact of the ill health of the soil on crop productivity and resource use efficiency reported in different parts of the world in recent years are also reviewed. The agro-techniques such as green and brown manuring in arable land and agroforestry on degraded and marginal land were followed on piece meal basis and for economic gain. The potential of these and several other options for maintaining soil need to be recognized, evaluated, and quantified for their wider application on the front of soil health management avenues. The use of crop residue, agro-industrial waste, and untreated mineral or industrial waste (basic slag, phosphogypsum, etc.) as soil amendments has a huge potential in maintaining healthy soil along with serving as sources of crop nutrition. The review emphasizes the evaluation and quantification of present-day followed agro-techniques for their contribution to soil health improvement across agro-climatic regions and for wider implications. Furthermore, emphasis is given to innovative approaches for soil health management rather than mere application of manures and fertilizers for crop nutrition.